The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s40195-020-01016-0
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Electromagnetic Properties of MgB2 Induced by Carbon-Containing Materials Addition and Process Techniques

Abstract: For the high transition temperature (T c ) and low cost taking both raw materials and fabrication process into account, MgB 2 has been a competitive candidate to replace the conventional NiTi superconductor for high-temperature application in fault current limiters, transformers, motors, magnetic resonance imaging, adiabatic demagnetization refrigerators, generators, etc. The carbon-containing materials addition induced high critical current density (J c ) is reviewed based on their influences on the upper cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 106 publications
1
1
0
Order By: Relevance
“…This indicates that the amino acids have induced some disorder especially in the a-b plane of the structure and much less along the c-axis direction. A similar behavior of the lattice parameters is generally observed when MgB2 is formed in the presence of organic additives [49][50][51][52][53][54][55] and this is attributed to the substitution of carbon atoms on boron sites in the lattice. A decrease of the a-axis lattice parameter has also been detected in studies of Mg-deficient MgB2 [56][57][58].…”
Section: Resultssupporting
confidence: 70%
“…This indicates that the amino acids have induced some disorder especially in the a-b plane of the structure and much less along the c-axis direction. A similar behavior of the lattice parameters is generally observed when MgB2 is formed in the presence of organic additives [49][50][51][52][53][54][55] and this is attributed to the substitution of carbon atoms on boron sites in the lattice. A decrease of the a-axis lattice parameter has also been detected in studies of Mg-deficient MgB2 [56][57][58].…”
Section: Resultssupporting
confidence: 70%
“…In conclusion, the diffusion distance of liquid Mg increased obviously, and more B powder could make contact with liquid phase, resulting in thicker MgB 2 layers. Moreover, it is concluded that the C coating is a credible carbon source that can acquire a more homogeneous doping effect because the C agglomeration impact is diminished [44].…”
Section: Evaluation Of Improved Mgb 2 Imd Wiresmentioning
confidence: 99%